DISKUSI KELOMPOK TERARAH - Edi Indrizal (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2014)
This article describes the FGD as data collection methods and techniques in social research and as part of a participatory approach to identify the circumstances, needs, problems and potential development opportunities into the community and social capital in development. In accordance with its use, is expected introductory discussion on this article in helping researchers understand the basics and implementation steps FGD as one of the research data collection techniques. Similarly for the practitioner community development facilitators to better facilitate group discussion as one of the expertise in running role as community care and development